Socio-Technical Power System Resilience (Global Journal of Computer Science and Technology, 2023)
Abstract Power systems serve social communities that consist of residential commercial and industrial customers The social behavior and degree of collaboration of all stakeholders such as consumers prosumers and utilities affect the level of pre- paredness mitigation recovery adaptability and thus power system resilience Nonetheless the literature pays scant attention to stakeholders social characteristics and collaborative efforts when confronted with a disaster and views the problem solely as a cyber-physical system However power system resilience which is not a standalone discipline is inherently a cyber-physical- social problem making it complex to address To this end in this paper we develop a socio-technical power system resilience model based on neuroscience social science and psychological theories and using the threshold model to simulate the behavior of power system stakeholders during a disaster
Keywords: resilience; social science; power systems; social computing; cyber-physical-social system; data science; social media; natural language processing